Research on the Effect of Executive Incentive Institutional Innovation on the Cost of Equity—Evidence From Chinese Listed Companies - Wang, Jin; Deng, Jie (Frontiers in Psychology, 2021)
Executive incentive has long been a hot topic among academics and practitioners. With the continuous development of China’s manager market, the spirit of innovation and entrepreneurship among executives has exerted a greater influence on corporate performance. Enterprise innovation is an important embodiment of the entrepreneurial spirit. Moreover, China’s supply-side reforms and state-owned enterprises compensation system have been advanced and innovated. Therefore, based on manager human capital theory and organizational innovation theory, and employing 15,492 firm-year observations from China’s Shanghai and Shenzhen A-share listed companies for the period 2005–2018, we construct various models, including the Gorden model, the Growth Rate of Price-Earnings Ratio model (PEG), the Ohlson and Juettner-Nauroth model (OJ), and the Capital Asset Pricing model (CAPM), to measure the cost of equity. We investigate the effect of the institutional innovation of executive incentives on the cost of equity, and the heterogeneous influence of China’s special property rights system on the relationship between the two. We find that the innovations of the executive incentive system have a positive governance effect on the cost of equity. In particular, executive compensation incentives significantly reduce a company’s equity costs. We also find that state-owned property rights may weaken the positive effect of institutional innovation of executive incentives. Furthermore, China’s executive incentives system and corporate governance mechanism are imperfect, thus, institutional innovation is a matter of great urgency; more innovative ideas for the manager market need to be introduced. China’s listed companies should give full play to the spirit of innovation and entrepreneurship, constantly innovating companies’ incentive-based compensation systems, and establishing a scientific and innovative concept of the cost of equity. The findings are robust after controlling for potential endogeneity concerns.